Protein undernutrition alters the colonic bacteriome, disrupts intestinal immune homeostasis, and impairs control of Leishmania infantum infection in a murine model of visceral leishmaniasis - Azevedo, Renata; Losada-Barragán, Monica; Costa, Erika M.; Pauer, Heidi; Hardoim, Cristiane Cassiolato Pires; Lima, Filipe; Pinho, Nathalia; Durães, Jonathan; Gaitán-Albarracín, Felipe; Cuervo-Escobar, Sergio; Arcila-Barrera, Sebastián; Umaña-Pérez, Adriana; et al. (Frontiers in Nutrition, 2026)
IntroductionUndernutrition is a significant global health issue that exacerbates susceptibility to infectious diseases, including visceral leishmaniasis (VL), caused by Leishmania infantum. Here, we investigated the interplay between undernutrition, immune responses, and the colonic microbiota composition in a murine model of VL.MethodsWe used BALB/c mice subjected to a low-protein diet and infected with L. infantum to analyze the effects on systemic and local immune responses, microbiota composition, and parasite load.ResultsUndernutrition significantly downregulated the mRNA expression of cytokines such as IFN-γ, IL-10, IL-12, and IL-17A in the colon while increasing the colonic luminal levels of proinflammatory cytokines, including TNF-α, CCL5, and IL-17A. The protein-deficient diet also induced dysbiosis, characterized by reduced Bacteroidota and increased Desulfobacterota and Firmicutes. Additionally, secretory IgA levels were markedly elevated in undernourished animals, suggesting a compensatory response to dysbiosis. The parasite load was significantly increased in the spleens of undernourished, infected mice, potentially due to disrupted immune-endocrine communication involving intestinal inflammation and microbial imbalance.DiscussionThese findings highlight the complex interplay between nutritional status, the microbiota, and host immunity in the progression of VL. Undernutrition exacerbates disease severity through local and systemic immune dysregulation and microbial shifts. Our results support new treatments targeting diet and microbiota to control VL.